2004
DOI: 10.1111/j.1492-7535.2004.0085ah.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frequent and Occasional Dialysis‐Associated Hypotension on Survival of Patients on Hemodialysis

Abstract: Atherosclerotic lesion of coronary artery frequently accompanies intimal hyperplasia of radial artery. We have reported that the lesion of radial artery (intimal hyperplasia) in hemodialysis (HD) patients is associated with early access failure (EAF) as well as ischemic heart disease (IHD) (Am J Kidney Dis. 2003; 41: 422-428). Objective: This study was designed to determine the impact of IHD on the EAF in nondiabetic HD patients. Methods: This study enrolled 125 nondiabetic HD patients who received radiocepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Earlier studies have demonstrated that survival of patients undergoing hemodialysis with DIH was significantly lower compared with those without DIH [2,3]. In agreement to these studies, we found that patients with DIH had higher mortality rates compared with those without DIH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Earlier studies have demonstrated that survival of patients undergoing hemodialysis with DIH was significantly lower compared with those without DIH [2,3]. In agreement to these studies, we found that patients with DIH had higher mortality rates compared with those without DIH.…”
Section: Discussionsupporting
confidence: 93%
“…It was associated with a significantly increased risk for mortality in patients undergoing hemodialysis [2,3]. DIH is the clinical manifestation of an imbalance between the decreased plasma volume during dialysis and the counter-regulatory cardiovascular haemodynamic and neurohormonal mechanisms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…first demonstrated that among a cohort of dialysis patients followed for 2 years, those that died during follow up had significantly lower nadir systolic BP than the survivors during a single initial treatment at the beginning of the study . In another cohort study, frequent episodes of intradialytic hypotension (more than 10 episodes over 10 months) were associated with significantly increased mortality risk compared to no intradialytic hypotension in unadjusted analyses; but, this failed to achieve statistical significance in fully adjusted models . The aforementioned study by Park et al.…”
Section: Intradialytic Hypotensionmentioning
confidence: 96%
“…There are two main clinical patterns of dialysis-associated hypotension : the first is episodic hypotension (defined by a sudden drop of systolic blood pressure below 100 mmHg or at least 30 mmHg with accompanying clinical symptoms), that typically occurs during the later stages of dialysis sessions and is generally favored by excessive weight gain ; the second is chronic persistent hypotension, which affects about 10% of long-term dialysis patients [1,2], most of whom experience frequent episodes of hypotension during dialysis sessions, whereas some patients have permanent hypotension with low predialysis systolic pressure, often less than 100 mmHg [3,4]. Intradialytic hypotension not only causes discomfort and has a negative impact on health-related quality of life but it may also adversely affect the outcome of chronic hemodialysis, reducing patients' life expectancy and favoring underdialysis [5][6][7][8][9][10]. According to recent data, low pre-dialytic systolic and diastolic pressures, like low post-dialytic systolic pressure and the occurrence of hypotensive episodes during dialysis sessions, are associated with a significantly increased risk of death [5][6][7][8][9].…”
Section: Definition and Epidemiology Of Dialytic Hypotensionmentioning
confidence: 99%